Facile Preparation and Properties of Crosslinked Copolyether Elastomers with 1,2,3‐Triazole and Urethane Subunit via Click Polymerization - Zhang, Qian (ChemistryOpen, 2019)
An azide terminated ethylene oxide‐tetrahydrofuran copolymer with urethane segments (ATUPET) as a novel binder pre‐polymer, has been prepared through ethylene oxide‐tetrahydrofuran random copolymer (PET) end‐capping modification via one‐pot method. The structure characterization of the modifier has been analyzed by FTIR, (1)H NMR, (13)C NMR and GPC. In comparison with PET, ATUPET has a slightly higher viscosity because it has additional hydrogen bonding interaction generated by the urethane in ATUPET. Triazole cross‐linked elastomers based on ATUPET with various functional molar ratios were prepared using tripropargylamine as a curing agent and cross‐linker. Mechanical properties indicate that the modulus E and tensile strength σ (b) exhibit a parabolic dependence with the increase in R. At around the stoichiometric ratio, the modulus E and tensile strength σ (b) reach a maximum and the elongation at break exhibit an acceptable value at the same time. Swelling tests demonstrate that the apparent cross‐linking densities (N(0)) have a maximum value at the stoichiometric ratio. Thermal analysis shows that the ATUPET prepolymer and its polytriazoles elastomers exhibit a satisfactory stability. The results demonstrated that ATUPET might be a promising polymeric binder for future propellant formulations especially in the field of isocyanate‐free curing technology.